MANAJEMEN PEMBELAJARAN DIGITAL BERORIENTASI MUTU: TINJAUAN INTEGRATIF TENTANG HASIL BELAJAR SISWA - Handayani, Surma; Aulia; Debi Rohilia Suherly; Husnul Aeni Hayati; Saskiya Suci Pebrikasih; Hamzah Fansuri; Muh. Fahrurrozi; Muhammad Sururuddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study synthesizes evidence on digital learning management mechanisms that support student learning outcomes and develops a quality-oriented implementation framework. An integrative literature review was conducted using empirical studies, systematic reviews, meta-analyses, policy reports, and official documents relevant to digital learning governance. Sources were selected according to relevance, publisher credibility, methodological transparency, verifiable metadata, and contribution to the review questions. Thematic analysis generated six dimensions: needs and readiness diagnosis; leadership, policy, and resource allocation; teacher competence and professional support; digital pedagogical design; implementation, interaction, and feedback; and monitoring, equity, safety, and continuous improvement. The findings indicate that digital technology does not automatically improve learning outcomes. Its contribution depends on goal alignment, active learning design, teacher-student interaction, timely feedback, teachers’ digital-pedagogical competence, sustainable infrastructure, and equitable access. Learning management systems, interactive multimedia, digital assessment, and gamification can strengthen flexibility, engagement, self-regulation, and academic achievement when governed as components of a learning system rather than as isolated tools. The study proposes a Quality-Oriented Digital Learning Management Framework linking organizational capacity, teacher practice, student experience, and learning outcomes through recurring cycles of diagnosis, action, evaluation, and improvement.